Examining the Role of Emotional Labor in Mediating the Relationship Between Calling and its Outcomes - Rawat, Anushri; Nadavulakere, Shiva (Journal of Applied Business and Economics, 2023)
Work as calling research has clearly established the benefits of having a calling, such as, work meaningfulness and job satisfaction, and is less forthcoming in identifying the affective linkages between calling and its outcomes. We propose that because individuals with high calling find their work purposeful and significant, they are more likely to actively shape their emotions and engage in emotional regulation. This study examines the role of emotional labor in mediating the relationship between calling and its two outcomes – emotional exhaustion and job performance. The data for the study included a sample of 195 teachers from 42 daycare centers. Findings suggest that having a high calling is associated with lower emotional exhaustion and is associated with higher job performance. Also, calling is significantly associated with emotional labor, and in particular, is positively related to deep acting and negatively related to surface acting. Further, results show that both surface acting and deep acting mediate the relationship between calling and its outcomes.